Expression of gamma secretase and notch signalling pathway in TS1CJE mouse model of down syndrome - Md Yusof, Hadri Hadi (2017)
Many medical complications such as hypotonia, congenital heart defects, intellectual disability and cognitive impairments are seen in Down syndrome (DS) individuals. Studies have shown that an increased glial-to-neuron ratio contributes to the intellectual disability of DS individuals. This neurogenic-to-gliogenic shift is characterised by an increased preference of neural progenitor cells committing to glial cell fate. To further understand the underlying mechanism of the shift, we utilised a mouse model for DS known as Ts1Cje that possesses a partial triplication of the mouse chromosome 16 (MMU16) that is syntenic to human chromosome 21 (HSA21). Ts1Cje have shown to have similar off balance cellular ratio in the brain. Notch signalling pathway is involved in the regulation of the proliferation of NPCs and inhibit neuronal cell commitment and promote glial cell fate. Notch protein is cleaved by gamma-secretase, a multi subunit transmembrane protein complex that releases the Notch intracellular domain (NICD) activating the downstream targets. The dysregulation of the gamma-secretase complex (Psen1, Ncstn, Aph-1b, Psenen) and Notch (Notch1 and Notch2) could lead to the imbalances seen in the brain of DS individuals. This study aims to profile the spatiotemporal gene expression of gamma-secretase and Notch signalling components during prenatal and postnatal timepoints in Ts1Cje mice. Gene expression analysis using RT-qPCR was done on embryonic brain samples (E10.5, E15.5, P1.5) and postnatal brain from three regions (cerebellum, cerebral cortex, and hippocampus) at four timepoints (P1, P15, P30, and P84). Results demonstrated inconclusive alterations in gene expression between Ts1Cje and wildtype mice due to the cellular heterogeneity of the samples. Results from RT-qPCR analysis from E15.5 neurosphere culture showed an increase of expression of Psen1, and Aph-1b genes instead of Notch signalling genes suggesting a potential dysregulation of gamma secretase regulated Notch-signalling pathway during early NPCs fate determination and differentiation. The western blot analysis of notch intracellular domain (NICD) however reveals decreased in Notch activation in Ts1Cje suggesting abnormal proteolytic processing of Notch prior to gamma-secretase cleavage. This data is supported by increased gamma-secretase activity using AlphaLISA assay in Ts1Cje embryonic neurosphere culture using artificial recombinant Notch substrate. This study suggests the potential role of Notch signalling and gamma-secretase in neurogenic-to-gliogenic shift through abnormal maintenance and proliferation of NSCs pool.